2007
DOI: 10.1007/s10620-006-9541-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Lens Culinaris Agglutinin-Reactive α-Fetoprotein and Des-γ-Carboxy Prothrombin in Histologically Proven Hepatocellular Carcinoma in the United States

Abstract: There is no established clinical role for the lens culinaris agglutinin-reactive fraction of alpha-fetoprotein (AFP-L3%) and des-gamma-carboxy prothrombin (DCP) in the management of the U.S. hepatocellular carcinoma (HCC) patient population. In order to clarify the clinical usefulness and characteristics of AFP-L3% and DCP, a prospective study was performed on United States patients having histologically proven hepatocellular carcinoma. Ninety-nine histologically proven HCC patients, who were diagnosed with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 49 publications
2
87
0
Order By: Relevance
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012). Other research studies (Riener et al, 2009;Hu et al, 2010) observed that GP-73 levels were significantly higher in patients with hepatitis C-derived HCC and a high tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012). Other research studies (Riener et al, 2009;Hu et al, 2010) observed that GP-73 levels were significantly higher in patients with hepatitis C-derived HCC and a high tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that a high DCP level correlates with invasiveness and the metastasizing property of carcinoma [2][3][4][5][6][7][8] . Shirabe et al [8] reported that the preoperative DCP level, tumor diameter, and histologic differentiation correlated with the presence or absence of microscopic vascular invasion in a study on 218 patients who had undergone hepatic resection.…”
Section: Discussionmentioning
confidence: 99%
“…An assay that employs higher DCP diagnostic sensitivity has been introduced [25,26] , but the diagnostic sensitivity for small hepatocellular carcinoma still remains at about 50% [27][28][29][30] . Thus, most reports on biological properties of DCP positive hepatic carcinoma are based on more advanced diseases [7] . Many reports state high DCP levels to be of poor prognostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, a-fetoprotein (AFP) is the generally accepted serological marker for HCC diagnosis, but sensitivity of the AFP assay is only 47% (The specificity is 96%) and cut-off value useful in tumor diagnosis is high (50 mg/L) [31]. Combined determination of AFP with AFP-L3 (Lens culinaris agglutinin reactive AFP), des-γ-carboxy prothrombin (DPC) could improve the sensitivity to 85% while the specificity would decrease to 59% [32,33].…”
mentioning
confidence: 99%